(untitled) (Experimental biology, 2023)
There was carried out research on genetic diversity of alloplasmic wheat lines that differ in resistance to drought and in terms of vegetation using markers for genes that determining the time of heading. The objects of research were nine allolines of wheat obtained by crossing T. dicoccum var Araratum (Host.) and T. aestivum sort of Mironovskaya 808, as a result was combination the cytoplasm of one species with the nuclear genome of another species and subsequent long-term selection. Using PCR analyze of Vrn and Ppd genes were conducted that determine the timing of heading. It has been found out that the majority of allolines for recessive vernalization and photoperiod genes inherit the genotype of the sort Mironovskaya-808. An exception is the D-n-05 line, in which the dominant allele Vrn-B1c has been identified.